2014
DOI: 10.1039/c3nj01523h
|View full text |Cite
|
Sign up to set email alerts
|

An α-MnO2nanotube used as a novel catalyst in ozonation: performance and the mechanism

Abstract: As a common monocomponent metal oxide, an a-MnO 2 nanotube was synthesized by a simple hydrothermal method and developed as an ozonation catalyst for the first time. a-MnO 2 nanotubes revealed excellent catalytic activity and stability for degradation of phenol in water. The strong interaction between ozone and a-MnO 2 in water was observed and confirmed as a critical step of catalysis. The IR analysis and the influence of phosphate showed that the surface hydroxyl groups and chemisorbed water acted as the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 43 publications
(45 reference statements)
1
40
0
Order By: Relevance
“…It was reported that ozone molecule attached with ␣-MnO 2 on its active sites detaches with another ozone molecule to produce oxygen and superoxide free radicals [37,38]. The ozone decomposed to oxygenated species, and superoxide radicals formed in this process was responsible for the efficient degradation of 4-NP [35,36].…”
Section: Reaction Mechanismmentioning
confidence: 98%
See 1 more Smart Citation
“…It was reported that ozone molecule attached with ␣-MnO 2 on its active sites detaches with another ozone molecule to produce oxygen and superoxide free radicals [37,38]. The ozone decomposed to oxygenated species, and superoxide radicals formed in this process was responsible for the efficient degradation of 4-NP [35,36].…”
Section: Reaction Mechanismmentioning
confidence: 98%
“…8). It was already reported that in the catalytic ozonation of phenols, hydroxyl radical is not the main active oxidant in 4-NP degradation [35]. Moreover, p-benzoquinone (p-BQ) was widely applied to quench superoxide radicals (O 2 −• ) to study its influence to the organics degradation [36,37].…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…6). Owing to the instantaneous reaction with hydroxyl radicals (3.8×10 8 -7.6×10 8 M -1 s -1 ) and the stagnated reaction with ozone (3 ×10 -5 M -1 s -1 ), tert-butanol (t-BA) was suggested to be the effective scavenger for •OH in the catalytic ozonation process 41. Addition of 12 mM t-BA brought no inhibition effect to the catalytic ozonation reaction, indicating •OH were not the reactive species for this catalytic ozonation system, which confirms the ESR results.The contribution of •O 2 -for PHBA degradation was determined using p-benzoquinone (p-BQ) as the quenching agent [42][43].…”
mentioning
confidence: 99%
“…In contrast, MnO 2 prepared by MnSO 4 The low capacity value of the compound could mainly be attributed to its agglomerated spherical particle morphology.…”
Section: Electrochemical Studiesmentioning
confidence: 93%